2013
DOI: 10.1111/acer.12167
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Up-Regulates the Expression of PDGF-β Receptor mRNA and Induces a Delayed PI3K-, AKT-, and p70S6K-Dependent Proliferative Response in Activated Hepatic Stellate Cells

Abstract: We conclude that liver injury up-regulates TGF-β1 that inhibits parenchymal cell proliferation, but stimulates HSC proliferation leading to the production of ECM and type I collagen resulting in fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 39 publications
4
32
0
1
Order By: Relevance
“…This was suggested by the fact that PDGF inhibitor, Crenolanib, reversed PEDF reduction caused by TGF-β. Our findings are consistent with prior results, were TGF-β1 was found to enhance PDGFR-β expression in hepatic stellate cells (32). Further analysis showed that PDGFR-β induction by TGF-β1 required PI3K, JNK1/2, p38 and to a lesser degree Erk1/2.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This was suggested by the fact that PDGF inhibitor, Crenolanib, reversed PEDF reduction caused by TGF-β. Our findings are consistent with prior results, were TGF-β1 was found to enhance PDGFR-β expression in hepatic stellate cells (32). Further analysis showed that PDGFR-β induction by TGF-β1 required PI3K, JNK1/2, p38 and to a lesser degree Erk1/2.…”
Section: Discussionsupporting
confidence: 94%
“…TGF-β is known to up-regulate PDGF receptors in hepatic cells (32). Similarly, PDGFR-β was significantly higher in primary fibroblasts treated with TGF-β (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our findings, a recent report showed that Raptor knock out mice were more susceptible to DEN-induced hepatic fibrosis and HCC [31]. Although the TGF-β1-mTORC1 axis plays essential roles for fibrogenesis in HSC [32, 33], we showed the presence of negative feedback regulation from mTORC1 to TGF-β1 signaling in this study (Supplementary Figure 6B). Activating this feedback regulation by BCAA could reduce the pro-fibrosis signaling in both HSC and hepatocytes that was observed in vitro and in vivo in this study.…”
Section: Discussionsupporting
confidence: 92%
“…GDF-15 leads to the extracellular matrix (ECM) accumulation in the mechanism: (1) directly increasing the synthesis of ECM components as procollagen 1a, (2) inhibition of tissue collagenases expression, (3) increasing synthesis of ECM-degrading enzyme inhibitors (as plasminogen activator inhibitor type 1, tissue inhibitors of metalloproteinases) 1820…”
Section: Discussionmentioning
confidence: 99%